Role of Integrin Alpha4 in Drug Resistance of Leukemia - Shishido, Stephanie; Bönig, Halvard; Kim, Yong-Mi (Frontiers in Oncology, 2014)
Chemotherapeutic drug resistance in acute lymphoblastic leukemia (ALL) is a significant problem, resulting in poor responsiveness to first-line treatment or relapse after transient remission. Classical anti-leukemic drugs are non-specific cell cycle poisons; some more modern drugs target oncogenic pathways in leukemia cells, although in ALL these do not play a very significant role. By contrast, the molecular interactions between microenvironment and leukemia cells are often neglected in the design of novel therapies against drug resistant leukemia. It was shown however, that chemotherapy resistance is promoted in part through cell-cell contact of leukemia cells with bone marrow stromal cells, also called cell adhesion-mediated drug resistance (CAM-DR). Incomplete response to chemotherapy results in persistence of resistant clones with or without detectable minimal residual disease (MRD). Approaches for how to address CAM-DR and MRD remain elusive. Specifically, studies using anti-functional antibodies and genetic models have identified integrin alpha4 as a critical molecule regulating bone marrow homing and active retention of normal and leukemic cells. Pre-clinical evidence has been provided that interference with alpha4-mediated adhesion of ALL cells can sensitize them to chemotherapy and thus facilitate eradication of ALL cells in an MRD setting. To this end, Andreeff and colleagues recently provided evidence of stroma-induced and alpha4-mediated NFkappaB signaling in leukemia cells, disruption of which depletes leukemia cells of strong survival signals. We here review the available evidence supporting the targeting of alpha4 as a novel strategy for treatment of drug resistant leukemia.